Design and Performance Analysis of a Single-Port Bidirectional Soft Actuator and Its Integration Into a Versatile 3-Finger Robot Gripper - Rene M. Suarez Flores; Sajid Nisar (IEEE Access)
This paper presents the design, fabrication, and characterization of a new soft robotic finger capable of bidirectional bending using single-port pneumatic actuation. Unlike the conventional soft pneumatic finger designs that require multiple input ports and/or actuation methods (i.e., positive and negative pressure), the proposed soft actuator uses a pre-curved body design to achieve bidirectional bending with a single port and a single actuation method (i.e., positive pneumatic pressure only), simplifying both fabrication and control. Finite Element Analysis is used to refine the finger design to achieve the desired bending capabilities and tip force. The finger prototype is fabricated using silicone casting, and its performance is characterized over a pressure range of 0-100 kPa. Experimental results demonstrate a bending range of 68° [ $- 34^{\circ } ~34^{\circ } $ ] for the applied pressure range and a maximum tip force of 2.72 N at 100 kPa. A three-finger robot gripper is developed, and grasping experiments are conducted to showcase the gripper’s ability to successfully grasp objects of various sizes, shapes, and textures. The bidirectional bending allows the gripper to grasp objects exceeding its normal grasp area three times (18 cm).